2011
DOI: 10.1007/s00467-011-1805-1
|View full text |Cite
|
Sign up to set email alerts
|

Medication beliefs and perceived barriers in adolescent renal transplant patients and their parents

Abstract: Understanding patient beliefs about medications and perceived barriers is important for optimal medical management. Differentiating adolescent views from parents' perceptions would enhance care by increasing communication about regimens and reducing obstacles. This study explored beliefs about medications and perceived barriers among 40 adolescent kidney transplant patients and their parents. Younger adolescents reported greater concern about medication harmfulness (t(38) = 2.190, p < 0.05) and more barriers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Findings related to adherence were similarly variable. In one US study, families with lower SES reported more barriers to their adolescent's medication taking 94 ; however, two US studies found no relation between SES and caregiver‐ or self‐reported adherence barriers 90,92 . Studies in Brazil 95 and the US 52 found higher income was associated with greater non‐adherence, while others in the US 88 and Guatemala 96 found no significant association between adherence and financial difficulties or income.…”
Section: Resultsmentioning
confidence: 95%
“…Findings related to adherence were similarly variable. In one US study, families with lower SES reported more barriers to their adolescent's medication taking 94 ; however, two US studies found no relation between SES and caregiver‐ or self‐reported adherence barriers 90,92 . Studies in Brazil 95 and the US 52 found higher income was associated with greater non‐adherence, while others in the US 88 and Guatemala 96 found no significant association between adherence and financial difficulties or income.…”
Section: Resultsmentioning
confidence: 95%
“…Weighing whether medications prescribed are necessary for one's physical well‐being while accepting the potential harmful side effects can be challenging for adolescents who want to feel and look normal in order to fit in with their peer group. In a prior study, younger adolescents expressed greater concerns about medications than older adolescents, with stronger beliefs about the harmfulness of their medications 25 . Among adults on dialysis and kidney transplant, 34.4% reported strong concerns about their medications (eg, long‐term effects, dependence) and 17.3% believed their medications to be harmful, while the majority (98.2%) strongly believed their medications to be necessary for their physical well‐being 26 .…”
Section: Beliefs About Medicinementioning
confidence: 94%
“…In a prior study, younger adolescents expressed greater concerns about medications than older adolescents, with stronger beliefs about the harmfulness of their medications. 25 Among adults on dialysis and kidney transplant, 34.4% reported strong concerns about their medications (eg, long-term effects, dependence) and 17.3% believed their medications to be harmful, while the majority (98.2%) strongly believed their medications to be necessary for their physical wellbeing. 26 Patient beliefs that medication is necessary was related to better adherence in dialysis patients 27 while lower perceived benefits, perceived harmfulness, and greater concerns about medication were associated with lower adherence in transplant samples.…”
Section: B Eliefs About Med I Cinementioning
confidence: 99%
“…They begin to assume responsibility for their healthcare and become less dependent on their families. It has been reported adolescent recipients after transplantation might have increased susceptibility to psychological illnesses and are prone to develop non-adherence to immunosuppressive medications, which might lead to rejection (35)(36)(37)(38). In the adolescent group, 40% (4/10) of patients with rejection eventually progressed to graft loss, whereas this number was 28.57% (4/14) in the child group and 6.25% (1/16) in the adult group.…”
Section: Discussionmentioning
confidence: 99%